“It's Frustrating, but…”: Brazilian and Indonesian Teachers’ Resilience to Assist Deaf Students’ Online Language Learning - Antonio Henrique Coutelo de Moraes; Rohmani Nur Indah (OKARA: Jurnal Bahasa dan Sastra, 2022)
Due to the recent increase in studies on emotions in Applied Linguistics and, especially now, in pandemic times, it opens more discussion to relate teachers' emotions with several other aspects including resilience. Therefore, this research aims to analyze language teachers’ experience in teaching deaf students in Recife, Brazil, and Malang, Indonesia. The methodology applied was qualitative. This study involved teachers in Recife, Brazil, and Malang, Indonesia. The teachers selected to be interviewed in this study were those who had experience teaching deaf students for at least five years and those who, during the pandemic times taught online. Two teachers were taken from each city. Findings point out, among other things, that decreasing the number of students per class and having parents involved in the process may help improve students' learning and teachers' experience and resilience. Based on the data on the implementation of language learning and the teachers' perception of the benefit, the constraints, and strategies in online language learning, resilience is triggered by the professional, personal, institutional, and community challenges.